Pan-African Women's Voices across Borders: Revisiting Theological Education in the Context of Feminized Migration - Adamavi-Aho Ekué, Amélé (The ecumenical review, 2019)
This article is structured from the epistemological vantage point of framing theological education within the context of Pan-African women's experiences of migration, where theological education is defined in the widest sense of creating knowledge, ethos, and practices from within different versions of Christian tradition, as opposed to transmitting a static corpus of knowledge. It begins by examining the deconstructive potential of Pan-African female migrants, particularly with regard to gendered patterns and projections of theological education. It then describes and analyzes the impact of Pan-African female migrants on the project of contextual theological education as an act of birthing and bringing to life the dimensions of seeing and interpreting the one life-giving story through the lenses of the lamenting, celebrating, and transforming stories of many. The article concludes by presenting Pan-African female migration as an opportunity to revisit theological education as a creative, ecumenical, and intercultural enterprise, seeing the empirical location of Pan-African female migrants as a paradigmatic lens for revisiting theological education as intercultural enterprise, and not (exclusively) as a contextual - and hence exceptional - historic experience.